Analisis Praktek Penjualan Para Pedagang Sembako Muslim Dalam Perspektif Etika Bisnis Islam (Studi Kasus Pedagang Muslim Sembako Di Pasar Tradisional Ambarketawang, Gamping Kabupaten Sleman) - Abd Adim; Abdul Salam (LAN TABUR : Jurnal Ekonomi Syariah, 2021)
Islam was taught that economic activities cannot be separated from the basic values set out in the Qur'an, the hadith of the Prophet and other sources of Islamic teachings, as in conventional economics, Islamic economic systems also talk about human activities to obtain and regulate material or non-material assets in order to meet the necessities of life as human beings both individually and collectively concerning the acquisition, distribution (trade) or use to fulfill living needs. It can be seen the Islamic economic system in Ambarketawang Traditional Market, Sleman Regency, where the majority of traders are Muslim.